2010
DOI: 10.1016/j.rfe.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Competitive conditions in Islamic and conventional banking: A global perspective

Abstract: I analyze the competitive conditions prevailing in Islamic and conventional global banking markets, and investigate the possible differences in profitability between these markets, using a sample of banks across 13 countries during 2000-2006. The results suggest that Islamic banks allocate a greater share of their assets to financing activities compared to conventional banks, and they are also better capitalized. Different computed measures of competition indicate that Islamic banking is less competitive compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
1
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(151 citation statements)
references
References 38 publications
3
137
1
10
Order By: Relevance
“…In addition, [13] also found that the profitability of the IBs significantly increased with market power, though this did not warrant higher profitability levels for the IBs.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, [13] also found that the profitability of the IBs significantly increased with market power, though this did not warrant higher profitability levels for the IBs.…”
Section: Introductionmentioning
confidence: 89%
“…However, IBs have been proven to be able to stay competitive with other CBs [13] in which the IBs allocated a greater share of their assets to financing activities compared to the CBs and that they were also better capitalised. In addition, [13] also found that the profitability of the IBs significantly increased with market power, though this did not warrant higher profitability levels for the IBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan (2010) investigates those features and questions to what extent Islamic banking and finance lives up to the ethical and moral practices of it and how different it is from conventional banking. Ariss (2010), analyzes Islamic and conventional banks across 13 countries for years between 2000 and 2006. She concluds that though it is less competitive, Islamic banking enables higher allocation of assets to the financing of projects by being better capitalized.…”
Section: Islamic Finance and Turkish Economymentioning
confidence: 99%
“…When P = MC, the Lerner index is zero and the firm has no pricing power. A Lerner index closer to one indicates the higher mark-up of price over marginal costs and hence market power for the firm (Ariss, 2010). In general, LI = 0 it indicates perfect competition, while LI = 1 indicates monopoly.…”
mentioning
confidence: 99%